Developing English for Specific Purposes (ESP) Textbook for Pharmacy Students Using On-Line Teaching in Higher Education - Abd. Syakur; Esti Junining; M. Khusni Mubarok; Margarana (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The purpose of this developmental research is to create ESP learning textbooks for Diploma three (D3) Pharmacy students at the Surabaya Pharmacy Academy, to determine the textbooks' feasibility, and to ascertain students' responses to the ESP textbooks. The ADDIE Research and Development (R&D) model is used in this study. This ESP textbook was created in response to the study's findings. The feasibility study of the ESP textbook reveals the following points: 1) The Diploma three (D3) Pharmacy program's material experts and lecturers assign a percentage of 53.33 percent below the range of 85.94 percent, indicating that the development of digital-based textbooks receives a "A" grade and falls into the "Very Good" category. 2) Media and digital experts with online learning as well as Pharmacy diploma three (D3) study programs provide a percentage of 53.33 percent less than the 85.94 percent range, indicating that developed digital-based textbooks receive a "A" and are classified as "Very Good." 3) Student comprehension, as measured by questionnaires, also received a favorable response of 53.33 percent in the range of 85.94 percent, indicating that the development of digital-based textbooks received a "A" or "Very Good" grade. The interviews revealed that students responded positively to digital-based ESP textbooks. In summary, the ESP textbook for Pharmacy students in the Diploma three (D3) department is acceptable which can be used as an online learning medium for English Teaching.